Exosomal circ_0093708 as a potential ferroptosis biomarker in cerebral ischemia–reperfusion injury - Ma, Shuyin; Zhang, Xiaodong; Fan, Jiaxin; Chen, Mengying; Yao, Qingling; Zhang, Nan; Shi, Kaili; Du, Shuang; Cheng, Yuxuan; Qu, Huiyang; Duan, Minyu; Yang, Han; et al. (Frontiers in Neurology, 2025)
BackgroundFerroptosis plays a critical role in neuronal injury following cerebral infarction. However, effective therapeutic strategies targeting ferroptosis after cerebral ischemia–reperfusion injury (CI/RI) remain limited. Exosome-based therapy holds significant promise in this context. This study aims to identify key exosomal markers of ferroptosis.MethodsBy integrating and analyzing multiple GSE datasets, we identified ferroptosis-associated key genes. These findings were further validated in external databases, cellular models, and animal experiments using malondialdehyde (MDA), glutathione (GSH), iron, reactive oxygen species (ROS) assays, qRT-PCR, Western blotting. By further establishing a ferroptosis model and inhibiting DUSP1 with drugs, we further explored the potential function of DUSP1 in ferroptosis. The role of miR-101-3p was assessed in CI/RI models, while the diagnostic value of exosomal circular RNA was evaluated using receiver operating characteristic curve analysis.ResultsCombined differential analysis revealed PTGS2 and DUSP1 as ferroptosis-associated genes potentially regulated by exosomal circRNAs. In cellular and animal models, ferroptosis post-CI/RI was confirmed by elevated MDA, iron, and ROS levels, alongside reduced GSH. DUSP1 expression was significantly upregulated during ferroptosis, as demonstrated by qRT-PCR, Western blotting, and immunofluorescence. In the simple ferroptosis model, the expression of DUSP1 increases and inhibiting DUSP1 can aggravate ferroptosis. Conversely, miR-101-3p was downregulated in CI/RI, consistent with database predictions. Notably, exosomal circ_0093708 exhibited high diagnostic accuracy (Area under the curve = 0.93, sensitivity = 90%, specificity = 90%). Bioinformatics analysis suggested binding interactions among circ_0093708, miR-101-3p, and DUSP1.ConclusionExosomal circ_0093708 is linked to DUSP1 and PTGS2 expression by sponging miR-101-3p, positioning it as a potential biomarker for ferroptosis in CI/RI.